Behavioural Biases and Mutual Fund Investment Decisions: The Role of Loss Aversion and Risk Perception - Radha, P; R, Manju Priya; Srividya, G. (NPRC Journal of Multidisciplinary Research, 2026)
Background: Traditional financial theories assume rational investor behavior, yet real-world evidence demonstrates that psychological factors significantly influence investment decisions. Behavioral finance has emerged to explain these deviations, particularly in mutual fund investments where emotional biases often lead to suboptimal outcomes. Objective: This study examines the impact of behavioral biases on mutual fund investment decisions, specifically focusing on loss aversion and risk perception. It aims to understand how these psychological factors influence fund selection, investment continuation, switching behavior, and redemption decisions among retail investors. Methods: A quantitative research design was employed using primary data collected through a structured questionnaire from 180 mutual fund investors in India. Respondents were selected through convenience sampling. Multiple regression analysis and chi-square tests were applied to examine the relationships between loss aversion, risk perception, and mutual fund investment decisions. Findings: Both loss aversion (β = -0.410, p < 0.001) and risk perception (β = -0.330, p < 0.001) have significant negative effects on mutual fund investment decisions, explaining 38% of the variance in investor behavior (R² = 0.38). Investors with high loss aversion and elevated risk perception demonstrate conservative decision-making, premature redemptions during market volatility, and inconsistent investment patterns that potentially undermine long-term wealth creation. Conclusion: Behavioral biases significantly shape mutual fund investment decisions, often leading investors to deviate from rational, long-term wealth-building strategies. Understanding these psychological influences is essential for improving investor outcomes and promoting disciplined investment behavior. Implementation: Financial advisors should provide behavioral counseling during market downturns, while asset management companies should simplify risk communication through scenario-based disclosures. Policymakers and regulators should support investor education programs focusing on bias awareness and long-term investing principles.